ERP Evidence for Scarce Rule Representation in Older Adults Following Short, but Not Long Preparatory Intervals - Czernochowski, Daniela (Frontiers in Psychology, 2011)
The focus of the present study was to examine the cognitive processes comprising advance preparation – rule representation, task-set updating and task-set reconfiguration - in young (20-25 years) and older adults (61-83 years). Specifically, this study aimed at further characterizing age-related differences in advance preparation, and evaluating how additional time to prepare might reduce behavioral costs in older adults. In line with previous findings, RT mixing costs were slightly larger for older compared to young adults, whereas behavioral switch costs were age-invariant. Following short preparation (600 ms), smaller antero-frontal ERP correlates for rule representation were associated with pronounced congruency costs in older adults. Centro-parietal ERP correlates of task-set updating and task-set reconfiguration were not delayed, but smaller in magnitude for older compared to young adults. Longer preparation (1200 ms) enabled older adults to re-activate relevant task rules, as evident in reduced congruency costs, and temporally sustained ERP correlates of task-set updating and rule representation well beyond 600 ms. Age-invariant switch costs appear related to additional, potentially compensatory frontal activity recruited by older adults to overcome difficulties in task-set reconfiguration.